2016
DOI: 10.1016/j.stem.2016.03.012
|View full text |Cite
|
Sign up to set email alerts
|

Expression Analysis Highlights AXL as a Candidate Zika Virus Entry Receptor in Neural Stem Cells

Abstract: Summary The recent outbreak of Zika virus (ZIKV) in Brazil has been linked to substantial increases in fetal abnormalities and microcephaly. However, information about the underlying molecular and cellular mechanisms connecting viral infection to these defects remains limited. In this study we have examined the expression of receptors implicated in cell entry of several enveloped viruses including ZIKV across diverse cell types in the developing brain. Using single cell RNA-Seq and immunohistochemistry, we fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

16
453
1
22

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 496 publications
(492 citation statements)
references
References 46 publications
16
453
1
22
Order By: Relevance
“…We reasoned that identifying cell types that are especially vulnerable to viral infection would facilitate studies of the viral life cycle, including entry mechanisms and host cell requirements. Building on studies that suggested that enriched expression of the candidate entry factor AXL could confer vulnerability to ZIKV entry (6-8), we used AXL expression levels to predict that radial glia, astrocytes, microglia, and endothelial cells would be particularly vulnerable to infection (9). A recent study highlighted the utility of ex vivo models using primary human tissue samples to analyze the consequences of ZIKV infection in the human prenatal brain (7).…”
mentioning
confidence: 99%
“…We reasoned that identifying cell types that are especially vulnerable to viral infection would facilitate studies of the viral life cycle, including entry mechanisms and host cell requirements. Building on studies that suggested that enriched expression of the candidate entry factor AXL could confer vulnerability to ZIKV entry (6-8), we used AXL expression levels to predict that radial glia, astrocytes, microglia, and endothelial cells would be particularly vulnerable to infection (9). A recent study highlighted the utility of ex vivo models using primary human tissue samples to analyze the consequences of ZIKV infection in the human prenatal brain (7).…”
mentioning
confidence: 99%
“…Con base en los resultados de estudios en cultivos celulares, Nowakowski, et al (41), han sugerido que los virus ZIKV, DENV y WNV pueden requerir receptores TAM para su fijaci贸n o entrada, y que la Axl actuar铆a como prote铆na de uni贸n y receptor de entrada. La caracterizaci贸n de la expresi贸n de Axl en c茅lulas madre neuronales fue el primer paso en la identificaci贸n de uno de los candidatos a ser el receptor de entrada del ZIKV (41).…”
Section: Discussionunclassified
“…Con base en los resultados de estudios en cultivos celulares, Nowakowski, et al (41), han sugerido que los virus ZIKV, DENV y WNV pueden requerir receptores TAM para su fijaci贸n o entrada, y que la Axl actuar铆a como prote铆na de uni贸n y receptor de entrada. La caracterizaci贸n de la expresi贸n de Axl en c茅lulas madre neuronales fue el primer paso en la identificaci贸n de uno de los candidatos a ser el receptor de entrada del ZIKV (41). Se ha detectado este receptor Axl, con actividad tirosina cinasa, en la se帽alizaci贸n mediada por los receptores TLR (toll like receptors), y resulta pertinente anotar que la v铆a de se帽alizaci贸n TLR3 se ha asociado con el da帽o celular inducido por el ZIKV, lo cual sugiere una relaci贸n entre el receptor Axl y la patogenia del Zika (42).…”
Section: Discussionunclassified
“…Several research groups applied the brain organoid model to study Zika infection, a current epidemic that has been strongly linked to newborn microcephaly 35, 46, 47, 48, 49, 50. These studies have provided evidence that human neural stem cells are selectively vulnerable35, 48 and more susceptible to premature differentiation50 upon Zika virus infection, providing a molecular explanation for the observed microcephaly.…”
Section: Translational Applications Of Brain Organoidsmentioning
confidence: 99%
“…A further study suggested activation of innate immune responses as a possible mechanism for Zika鈥恑nduced neuroprogenitor cell death 47. In addition, organoid model has been used to identify putative receptor proteins mediating Zika entry into the nervous system 49. Most recently, brain organoids were used to validate potential repurposed drugs for treating Zika infections 51…”
Section: Translational Applications Of Brain Organoidsmentioning
confidence: 99%